The ORGAN SIZE (ORG) locus modulates both vegetative and reproductive gigantism in domesticated tomato - Vicente, Mateus H.; MacLeod, Kyle; Zhu, Feng; Rafael, Diego D.; Figueira, Antonio; Fernie, Alisdair R.; Mohareb, Fady R.; Kevei, Zoltan; Thompson, Andrew J.; Zsögön, Agustin; Pereira Peres, Lázaro Eustáquio (Oxford University Press, 2023)
Background and Aims Gigantism is a key component of the domestication syndrome, a suite of traits that differentiates crops from their wild relatives. Allometric gigantism is strongly marked in horticultural crops, causing disproportionate increases in the size of edible parts such as stems, leaves or fruits. Tomato (Solanum lycopersicum) has attracted attention as a model for fruit gigantism, and many genes have been described controlling this trait. However, the genetic basis of a corresponding increase in size of vegetative organs contributing to isometric gigantism has remained relatively unexplored. Methods Here, we identified a 0.4-Mb region on chromosome 7 in introgression lines (ILs) from the wild species Solanum pennellii in two different tomato genetic backgrounds (cv. ‘M82’ and cv. ‘Micro-Tom’) that controls vegetative and reproductive organ size in tomato. The locus, named ORGAN SIZE (ORG), was fine-mapped using genotype-by-sequencing. A survey of the literature revealed that ORG overlaps with previously mapped quantitative trait loci controlling tomato fruit weight during domestication. Key Results Alleles from the wild species led to lower cell number in different organs, which was partially compensated by greater cell expansion in leaves, but not in fruits. The result was a proportional reduction in leaf, flower and fruit size in the ILs harbouring the alleles from the wild species. Conclusions Our findings suggest that selection for large fruit during domestication also tends to select for increases in leaf size by influencing cell division. Since leaf size is relevant for both source–sink balance and crop adaptation to different environments, the discovery of ORG could allow fine-tuning of these parameters.
Keywords: cell division; cell expansion; domestication; fruit size; gigantism; organ size; Solanum; tomato; wild relatives